The Start of the State Program of CW Destruction in Russia - S. V. Petrov (Вестник войск РХБ защиты, 2023)
The last chemical munition from Russian arsenals of chemical weapons has been destroyed September 22, 2017, at the Kizner facility in Udmurtia. Chemical weapons (CW) destruction started at the times of the demise of the USSR and the change of political formation in the country, followed by the collapse of its economy. Russian Federation Government Decree № 305, «On the Approval of the Special Federal Targeted Program for the Destruction of Chemical Weapons Stockpiles in the Russian Federation» (21 March 1996), became an important milestone in Russia`s fulfilling its international commitments, including its chemical weapons disarmament obligations. Due to certain Soviet scientific and technological advances and thanks to the extraordinary efforts and talent of the experts from the Radiological, Chemical and Biological Defence Troops of the Armed Forces of the Russian Federation, from the Federal Agency for the Safe Storage and Destruction of Chemical Weapons and from several other scientific research organizations, the CW destruction program has been completed three years ahead of schedule. Two-stage process of chemical neutralization, technically adapted to different types and ways of CW stockpiling, have been used for CW destruction. Seven special facilities have been built in Gorny (Saratov region), Kambarka and Kizner (Udmurt Republic), Maradykovsky (Kirov region), Shchuch'ye (Kurgan region), Leonidovka (Penza region) and Pochep (Bryansk region) for this purpose. 40,000 metric tons of CW have been destroyed at these facilities. The implementation of the Federal Targeted Program three years ahead of schedule saved considerable financial resources for the country and saved the population of the regions where CW stockpiling and destruction facilities have been located, from serious danger in case of any incident or accident.